EP355/#485 Extended genotyping as triage of hpv positive screened women in low-middle income countries (LMIC). (4th December 2022) - Merwe, Frederick Van Der; Botha, Matthys; Dreyer, Greta; Snyman, Leon; Visser, Cathy; Adams, Robyn; Richter, Karin; Dreyer, Gerrit J
Abstract : Objectives: Cervix cancer screening with HPV testing is widely accepted. The ideal triage test of screen positive women should identify those at highest risk of CIN2+ and avoid overtreatment of those with lesions <CIN2. We evaluated extended genotyping on the Xpert® HPV platform as triage test. Methods: A total of 1063 women, aged 25–65 years with no screening in the preceding five years were screened and genotyped with an Xpert® HPV test. The 14 targeted HPV types are detected in five fluorescent channels: HPV16; HPV18/45; HPV31/33/35/52/58; HPV51/59; and HPV39/56/66/68. Biopsies were performed on all HPV+ women. Results: A total of 454 participants were HIV+ (WLWH) and 609 were HIV-. Overall HPV prevalence was 34.0%. The prevalence was significantly higher in WLWH compared to HIV- women (48.9% vs 22.8%). This was consistent over all channels. CIN2+ prevalence amongst all participants was 32.74% (n=348), 44.93% (n=204) amongst WLWH and 23.65% (n=144) amongst HIV- participants. The absolute risk (PPV) of CIN2+ for channels 1&2, channel 3 and channels 4&5 were 81.12%, 62.50% and 30.77% respectively. Corresponding PPV for WLWH were 87.10%, 68.97% and 31.03% respectively and for HIV- women 70.00%, 51.02% and 30.43% respectively. Conclusions: Extended genotyping identified women who tested positive in the first 3 channels to be at highest risk for CIN2+. These women could be directly referred for treatment. Women testing positive for channels 4 and 5 should either be subjected to a second triage test or followed up.